A Kinetically Superior Rechargeable Zinc-Air Battery Derived from Efficient Electroseparation of Zinc, Lead, and Copper in Concentrated Solutions - Chen, Peng; Wang, Xia; Li, Dongqi; Pietsch, Tobias; Ruck, Michael (Chemsuschem, 2022)
Zinc electrodeposition is currently a hot topic because of its widespread use in rechargeable zinc-air batteries. However, Zn deposition has received little attention in organic solvents with much higher ionic conductivity and current efficiency. In this study, a Zn-betaine complex is synthesized by using ZnO and betainium bis[(trifluoromethyl)sulfonyl]imide and its electrochemical behavior for six organic solvents and electrodeposited morphology are studied. Acetonitrile allowed dendrite-free Zn electrodeposition at room temperature with current efficiencies of up to 86 %. From acetonitrile solutions in which Zn, Pb, and Cu complexes are dissolved in high concentrations, Zn and Pb/Cu are efficiently separated electrolytically under potentiostatic control, allowing the purification of solutions prepared directly from natural ores. Additionally, a highly flexible Zn anode with excellent kinetics is obtained by using a carbon fabric substrate. A rechargeable zinc-air battery with these electrodes shows an open-circuit voltage of 1.63 V, is stable for at least 75 cycles at 0.5 mA cm−2 or 33 cycles at 20 mA cm−2, and allows intermediate cycling at 100 mA cm−2.
CRIS-Team Scopus Importer:2023-03-20
Keywords: batteries; electroseparation; kinetics; solvent effects; zinc